Did the Debt Crisis Cause the Investment Crisis? - Warner, A. M. (Quarterly Journal of Economics, 1992)
There is now a large literature that attributes the investment decline in heavily indebted countries to the effects of the international debt crisis which began in 1982. However, these countries also faced falling export prices and high world real interest rates in the early 1980s, and these shocks could have directly caused investment to decline. One way to test for debt effects is to see whether equations without any debt-related information can nevertheless forecast the investment declines that these countries experienced. This paper shows that such equations can forecast investment in many indebted countries, and thus casts doubt on many debt-related explanations for the investment declines. I.